STUDY OF THE POTENTIAL AND DEVELOPMENT OF RENEWABLE ENERGY POWER IN INDONESIA : A REVIEW - Fajar Paundra; Akhmad Nurdin (Steam Engineering, 2022)
Energy consumption in Indonesia every year shows an increasing trend, with energy sources from fossils or non-renewable energy dominating renewable energy in the national energy mix. Climate change due to fossil energy emissions and the depletion of fossil energy reserves directly encourages Indonesia to develop and utilize renewable energy, which is abundantly available in Indonesia. The purpose of this study is to examine the development and planning of the contribution of renewable energy in each sector to the national energy mix in the short to long term. Geothermal capacity total installed in 2019 2130.7 MW with a plan 7.2 GW in 2025 and 17.6 GW in 2050, hydropower total capacity in 2019 6283.3 MW with a paln 21 GW in 2025 and 41 GW in 2050, bioenergy total ini 2019 for power generator 2200 MW with a plan 5.5 GW in 2025 and 26 GW in 2050, in solar energy total capacity in 2020 as power plant 17.22 MW with a plan 6,5 GW in 2025  and 45 GW in 2050, in wind energy until 2020 total capcity for electrical energi 153. 83 MW with a plan 1.8 GW in 2025 and 28 GW in 2050, and the marine energy energy sector in Indonesia has not yet been utilized as an energy harvester. In general, the government targets an increase in the percentage of renewable energy in the national energy mix in the short term until 2025 with a 23% contribution, and in the long term until 2050 with a 31% contribution.